Management of palatal perforation in systemic lupus erythematosus patient - Dwi Setianingtyas; Paulus Budi Teguh; W Widyastuti; Neken Prasetyaningtyas; Ramadhan Hardani Putra; Felicia Eda Haryanto (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disease which damages tissues and causes chronic inflammation with an idiopathic etiology. It has been suggested that oral lesions in patients with SLE can be grouped clinically as erythema, discoid lesions and oral ulcerations. The latter have been said to indicate the onset of a severe systemic disease flare and that oral ulcers represent cases of mucosal vasculitis. Palatal lesions generally present in the form of ulcers or, in more severe forms, as perforation. Acquired palatal perforations can be caused by several etiologies including: developmental disorders, malignancy and infections. Purpose: To report the management of palatal perforation in an SLE patient. Case: A 14-year-old female patient attended the Dr. Ramelan Naval Hospital, with both a perforated palate that often caused her to choke when eating or drinking and maxillary anterior tooth mobility. Case Management: The treatment for the patient in this case consisted of debridement and DHE, pharmacological therapy including aloclair gel and minosep mouthwash to maintain oral hygiene and prevent re-infection. At the end of the first consultation, the patient was prescribed an obturator in order to avoid oro-anthral infection. During the second consultation, the patient’s orthodontic bracket was removed to facilitate scaling and splinting of the anterior maxillary teeth carried out to prevent their movement. During the third consultation, a swab was taken by an oral surgeon who also administered antifungal therapy. During the fourth and final consultation, the patient was examined a prosthodontic specialist due to an obturator which was causing discomfort. Conclusion: The management of palatal perforation lesions in an SLE patient requires a multidisiplinary approach.